Penggunaan Buah Maja sebagai Pupuk Organik dan NPK Mutiara terhadap Pertumbuhan Kacang Hijau di Kabupaten Serdang Bedagai - Sari, Putri Mustika; Siregar, Mawaddah Putri Arisma; Lisa, Oviana (Agrosains : Jurnal Penelitian Agronomi, 2022)
Indonesia has experienced a decline in green bean production due to unsuitable green bean cultivation and low soil fertility. However, combining NPK Mutiara and organic fertilizer made from active maja fruit containing NPK Mg and Fe can increase soil fertility and quality in an environmentally friendly way. This study aims to examine the effect of combining organic fertilizers with active ingredients of maja fruit and pearl NPK in increasing the growth of green bean varieties of VIMA-1. The research was carried out in Sukajadi Village, Perbaungan, Serdang Bedagai District, from October to December 2021 using a 2-factor RAK design where the first factor was PO application with four treatment levels, namely M0 = Control; M1 = 100ml PO: 750 ml water; M2 = 100 ml PO: 1500 ml water; M3 = 100 ml PO: 2250 ml water. Then the second factor is the dose of NPK Mutiara fertilizer where P1 = 30g/plot and P2 = 40g/plot with the number of replications 3. The results showed that the administration of PO with the active ingredient of maja fruit had an insignificant effect on all parameters observed. However, the NPK fertilizer treatment had a significant impact on diameter. Stems at treatment P1 = 30g/plot.